Two kinds of meaningful multimedia learning: Is cognitive activity alone as good as combined behavioral and cognitive activity?. (April 2018) - Skuballa, Irene T.; Dammert, Anke; Renkl, Alexander
Abstract: Learners should become cognitively active to profit from multimedia representations. However, whether novices' cognitive engagement should be augmented by behavioral engagement during multimedia learning is controversial. We find support for both stances in the literature: high cognitive engagement and high cognitive-plus-behavioral engagement. We investigated the effectiveness of two types of prompts corresponding to these stances. Study 1 (44 8th-graders) tested a group with think prompts versus a group with think-and-do prompts, whereas Study 2 (94 8th-graders) aimed to additionally investigate whether prompts per se revealed an effect. Although prompts prolonged learning time, think prompts promoted knowledge acquisition. Our findings show that learners who engaged in cognitive activity outperformed those who were prompted for cognitive and behavioral engagement. Pure cognitive engagement benefited retention, transfer, and the retrieval of information focused by prompts. We discuss reasons why behavioral engagement can be detrimental. Highlights: Prompting students in cognitive activity and cognitive activity plus behavioral activity fosters meaningful learning. There is no effect of prompting in general, instead the type of prompt is pivotal. Novice learners profit only from prompts promoting cognitive activity. Prompting learners to engage in additional behavioral activity, in form of highlighting, impedes comprehension Overall, learning with prompts is time-consuming.